The Impact of Financial Ratio toward Stock Return of Property Industry in Indonesia - Stefano, Kevin (iBuss Management, 2015)
Indonesia property industry is one of the most booming sectors in recent years. The growth of property companiesâ stock return is higher than overall stock index after 2009. This research is conducted to identify whether financial ratio, as a representative of companies financial performance, has significant impact toward the booming stock return of property industry. TheÂ dataÂ wasÂ gatheredÂ usingÂ judgement samplingÂ byÂ generating the financial ratio of 18 property companies listed in Indonesia Stock Exchange. The data was analyzed by using Multiple Linear Regression Analysis. TheÂ resultÂ showsÂ thatÂ financial ratio simultaneously have significant impact toward the stock return.Â Meanwhile, i n d i v i d u a l l y , only Return on Asset has the significant impact toward stockÂ return of property industry in Indonesia. Keywords: Financial Ratio, Stock Return, Property Industry, Indonesia